Progresivitas Hakim dalam Menentukan Beban Akibat Perceraian Bagi Suami Kepada Istri Pasca Perceraian - Alfina Sauqi Anwar (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2021)
There are variation of Judges in determining husband’s obligatory burden toward their wives due to divorce because there is no provision which specially regulate every Judges to determine the amount of the sustenance post divorce. this article describe about how the progression of judges in determining the obligatory burden due to divorce for the husband toward their ex wives. this is a literature study which take the source from Directory of Supreme Court Decision in the First, Appeal and Cassation Level. this study will describe about how the judges in Religious Justice Agency especially Supreme Court in making effort to protect women’s rights post divorce. this sutdy will analyze about Judges’ decision which charge the husbands to fulfill their obligation toward their ex wives in the form of Iddah, Madliyyah and Mut’ah living. the next discussion is about  how the judges apply the progressive law through their decision that is, obligation which is charged to the husband in fulfilling their ex wives’ rights post divorce.   Hakim dalam menentukan beban terhadap suami kepada istri akibat perceraian bervariatif dan belum ada ketentuan khusus yang mengatur secara rinci bagi hakim dalam menentukan besar kecilnya besaran nafkah pasca perceraian. Artikel ini menguraikan tentang bagaimana progresifitas hakim dalam menetapkan beban akibat perceraian bagi suami terhadap istri yang diceraikan. Tulisan ini bersifat literer yang bersumber dari Direktori Putusan Mahkamah Agung pada Tingkat Pertama, Tingkat banding, dan Tingkat Kasasi. Tulisan ini akan menguraikan tentang bagaimana hakim pada badan Peradilan Agama khususnya Mahkamah Agung dalam melakukan upaya melindungi hak-hak perempuan pasca perceraian. Tulisan ini akan menganalisa tentang putusan hakim yang membebankan suami untuk  memenuhi kewajiban kepada istri berupa pembayaran nafkah iddah, nafkah madliyyah, dan mut’ah. Pembahasan selanjutnya tentang bagaimana hakim telah menerapkan hukum progresif melalui putusannya yaitu, kewajiban yang dibebankan hakim kepada suami dalam hal pemenuhan hak istri pasca perceraian.